2021
DOI: 10.3390/ma14206104
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Thermal Shock Damage Behavior in CVI SiC/SiC High-Pressure Turbine Twin Guide Vanes

Abstract: In this paper, the SiC/SiC high-pressure turbine twin guide vanes were fabricated using the chemical vapor infiltration (CVI) method. Cyclic thermal shock tests at different target temperatures (i.e., 1400, 1450, and 1480 °C) in a gas environment were conducted to investigate the damage mechanisms and failure modes. During the thermal shock test, large spalling areas appeared on the leading edge and back region. After 400 thermal shock cycles, the spalling area of the coating at the basin and back region of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Figure 4A shows the aerodynamic load analysis of the guide vane. The maximum aerodynamic pressure occurred at the basin region of the guide vane, 8 and the value was σ = 1.6 MPa. The pressure at the back region of the guide vane was relatively low.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 4A shows the aerodynamic load analysis of the guide vane. The maximum aerodynamic pressure occurred at the basin region of the guide vane, 8 and the value was σ = 1.6 MPa. The pressure at the back region of the guide vane was relatively low.…”
Section: Resultsmentioning
confidence: 98%
“…CMCs become the most promising alterative materials for advanced aero engine turbine parts 4–7 . The turbine parts work in a very harsh environment, that is, high temperature, thermal fatigue, thermal shock, and susception to oxidation and thermal corrosion 8 . Under the support of NASA's Ultra Efficient Engine Technology (UEET) program, Pratt & Whitney (P&W) and United Technologies Research Center (UTRC) designed and developed SiC/SiC turbine guide vanes (TGVs), which consisted of six plies of Sylramic SiC fiber cloth reinforced with chemical vapor infiltration (CVI) and melt‐infiltrated SiC matrix 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The C/SiC ceramic-matrix composites (CMCs) have excellent properties such as high-temperature resistance, thermal shock resistance, high strength, toughness, hardness, wear resistance, chemical stability, design tolerance, and low density and thermal expansion coefficients [ 1 , 2 , 3 , 4 , 5 ]. It can meet the requirements of long service life at a high temperature of 1650 °C and has broad application prospects in high thrust-to-weight ratio (TWR) aero engines, hypersonic ramjet engines, space shuttle thermal protection systems (TPS), and so on [ 6 , 7 , 8 , 9 , 10 ]. The HERMES, MSTP, ARD, GSTP, and FLPP programs of the European Space Agency (ESA) and the NASP, ISTP, Future-X, Hyper-X, and OTV programs of NASA have carried out relevant research and demonstration verification tests on C/SiC TPS.…”
Section: Introductionmentioning
confidence: 99%
“…SiC/SiC ceramic-matrix composites (CMCs) have already been applied in hot-section components of gas turbine engine, e.g., turbine guide vanes and blades, combustion chamber. 1-6…”
Section: Introductionmentioning
confidence: 99%
“…SiC/SiC ceramicmatrix composites (CMCs) have already been applied in hot-section components of gas turbine engine, e.g., turbine guide vanes and blades, combustion chamber. [1][2][3][4][5][6] Under tensile loading, matrix cracking and opening occur at low applied stress. [7][8][9] Forna-Kreutzer et al 10 observed the interface cracks, inclined cracks, and crack opening behavior in Nextel TM 720/Alumina oxide-oxide composite at room temperature and 1050 o C using X-ray computed micro-tomography (XCT) and digital volume correlation (DVC).…”
Section: Introductionmentioning
confidence: 99%